(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The word AI is derived by Artificial Intelligence has the potential to improve the quality of man’s intellectual power in modern day. This is the intertwined method to bring excitement for coming out information and its spread all over the world with in a small second. Virtually the man knowledgeable in AI make man perfect which trained in intelligence behavioral knowledge of algorithm. So, the main themes of this paper is to known about AI (Artificial intelligence) in Biological Science in NEP, 20-20.